The Use of Modulation as a Strategy of Translating Humour Sense in Obama’s Speech - محمد، افان صبحي; ياسين، أحمد حساني (الجامعة العراقية - مركز البحوث والدراسات الإسلامية, 2023)
أجريت هذه الدراسة لبيان استخدام التحوير في تحويل الحس الفكاهي عند باراك أوباما. وتهدف هذه الدراسة إلى الكشف عن كيفية استخدام طلبة الماجستير للتحوير كاستراتيجية مناسبة في ترجمة خطاب أوباما. أن البيانات المختارة هي خطاب لأوباما في أحد خطاباته لعشاء المراسلين في البيت الأبيض. ويتكون نموذج الدراسة من مرحلتين أساسيتين، الأولى هي النمذج اللغوي الذي اقترحه فيركلاف (١٩٩٥، ۲۰۰۳، ۲۰۱۰)، أما الثاني فيتعلق برواد الترجمة فيناي وداربلنت (1958، 1995). وتخلص هذه الدراسة إلى أن طلبة الماجستير في قسم الترجمة يستخدمون استراتيجية التحوير لترجمة خطاب أوباما أكثر من الاستراتيجيات الأخرى. This study is conducted to show the use of modulation in translating humour sense in Obama’s speech, It aims to reveal how the M.A. students use modulation as a suitable strategy in translating Obama’s speech. The data selected is a speech of Barak Obama at correspondent dinner in White House. In this study, the models consist of two adopted phases, the first one is the linguistic model proposed by Fairclough (1995, 2003, 2010), the second one is related to the pioneers of translation Vinay and Darbelnet (1958-1995). This study concludes that M.A students use modulation strategy of translating Obama’s speech more than other strategies.
Keywords: الخطابات السياسية -- ترجمة الحس الفكاهي -- باراك حسين أوباما، رئيس أمريكا